2003
DOI: 10.1148/radiol.2271020288
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic US of the Anterior Band of the Ulnar Collateral Ligament of the Elbow in Asymptomatic Major League Baseball Pitchers

Abstract: Dynamic US provides a rapid means for evaluating the anterior band of the UCL in professional baseball pitchers. In pitching arms, this band is thicker, is more likely to have hypoechoic foci and/or calcifications, and demonstrates more laxity with valgus stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(209 citation statements)
references
References 24 publications
7
200
2
Order By: Relevance
“…It originates from the medial epicondyle and inserts distally at the base of the coronoid process. The anterior band is the primary restraint to valgus stress [10] and originates from the anteroinferior margin of the medial epicondyle inserting onto the sublime tubercle of the ulna. The ulnar nerve passes through the medial intermuscular septum, approximately 8 cm above the medial epicondyle, coursing along a groove in the medial head of triceps.…”
Section: Anatomy and Pathogenesismentioning
confidence: 99%
“…It originates from the medial epicondyle and inserts distally at the base of the coronoid process. The anterior band is the primary restraint to valgus stress [10] and originates from the anteroinferior margin of the medial epicondyle inserting onto the sublime tubercle of the ulna. The ulnar nerve passes through the medial intermuscular septum, approximately 8 cm above the medial epicondyle, coursing along a groove in the medial head of triceps.…”
Section: Anatomy and Pathogenesismentioning
confidence: 99%
“…Sasaki et al 22) reported dynamic ultrasonography for evaluating medial joint laxity and medial collateral ligament injury revealed that the medial elbow joint gap and angular deformity was more increased in the dominant arm of 30 male baseball pitchers. Nazarian et al 23) examined the medial collateral ligament of 26 professional baseball players using dynamic ultrasonography, who had no symptoms on their elbow, and revealed both low echogenic lesions or calcification and thick bands on pitchers'…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrating pathological changes in common extensor tendon, ulnar collateral ligament or heel tendon have been reported [10][11][12][13][14] . However, there were limited studies investigating the role of ultrasonography in lateral epicondylitis [1,4,10,12] .…”
Section: Ultramentioning
confidence: 99%